J. O. Halliwell-Phillipps correspondence - Halliwell-Phillipps, J. O. (James Orchard), 1820-1889.
ALS with cover (12 January 1883; Hollingbury Copse, Brighton, Eng.) from Halliwell-Phillipps to Edward G. Allen, Covent Garden, London, Eng., discussing the Shakespeare-Bacon controversy.
Scholar and librarian.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Allen, Edward G. -- Correspondence; Bacon, Francis, -- 1561-1626 -- Authorship; Shakespeare, William, -- 1564-1616 -- Authorship -- Baconian theory; English drama -- Authorship; Librarians; Scholars